Training and Introduction to Physical Education and Sports Modification Media for Physical Education and Sports Teachers in the Village Tembung District of Percut Sei Tuan - Muhammad Noer Fadlan; Ahmad Landong (Journal of Community Service For Indonesian Society, 2023)
This article discusses training and the introduction of modified physical education and sports media for teachers in sports education subjects, while this training was conducted in Tembung Village, Precut Sei Tuan District, in the training process the author found several problems before conducting the training, including several problems there are still teachers who often carry out learning processes that tend to be monotonous, so that students tend to feel bored doing learning in the classroom. The training method used is lectures, then the techniques in the data collection process are supported by descriptive quantitative methods where the process of implementation is carried out by presenting the data that has been analyzed. Then after the training the results were found that the teachers were much more successful and could interpret the training and learning process more pleasantly, meaning that the teachers understood much better how to modify good learning, so that the learning process was much more enjoyable.